Characterisation of starved hydrodynamic lubricating films. (March 2019) - Liu, C.L.; Guo, F.; Wong, P.L.
Abstract: Optimisation of lubricant supply to bearings has considerable benefits in terms of energy saving and smooth running. This paper presents a study on the hydrodynamic lubrication of sliding contact with various supplied lubricant quantities. Experiments were conducted with an optical slider-bearing test rig. Under limited lubricant supply (LLS), there exists a critical speed beyond which film thickness no longer increases with increasing speed due to starvation at the inlet. The critical speed significantly depends on lubricant quantity, as well as lubricant viscosity and load. Comparison between experimental and theoretical results indicates that the starved films have certain load-carrying capacity and viscous resistance. Under LLS, film thickness is a sensitive function of supply lubricant volume, but friction is not. Highlights: Hydrodynamic lubrication under limited lubricant supply (LLS) is studied. LLS lubricating films are characterised in terms of friction and film thickness. It confirms that LLS films have load-carrying capacity and viscous resistance. LLS film thickness is a strong function of supply volume, but friction is not. Beyond a critical speed, LLS film thickness is steady and independent of speed.